2004
DOI: 10.1038/sj.hdy.6800521
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale estimation of outcrossing in western redcedar with microsatellite assay of bulked DNA

Abstract: Western redcedar (Thuja plicata, Cupressaceae) is a selffertile conifer with a mixed mating system and significant variation for outcrossing among populations. In this paper, we conducted a fine-scale study of mating system variation to identify correlates of outcrossing in natural populations. We examined variation for outcrossing within and among individual trees, and describe a new method to estimate outcrossing using bulked DNA samples. Bulking (assaying DNA tissues from several individuals simultaneously)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
2
19
1
1
Order By: Relevance
“…The positive relationship between tree and crown size and outcrossing rates suggested that the proportion of outcrossed pollen reception might be enhanced in bigger trees with ample crowns, decreasing selfing rates. However, O'Connell et al (2004) observed that outcrossing rates decreased with increasing tree height in four populations of Thuja plicata. This variety of results emphasizes the idea that tree size, apart from directly affecting outcrossing rates through increasing flower exposition to the pollen cloud, may also be a gauge for other factors affecting mating patterns, such as reproductive effort or tree social position within the stand (Burczyk et al, 1996;González-Martínez et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The positive relationship between tree and crown size and outcrossing rates suggested that the proportion of outcrossed pollen reception might be enhanced in bigger trees with ample crowns, decreasing selfing rates. However, O'Connell et al (2004) observed that outcrossing rates decreased with increasing tree height in four populations of Thuja plicata. This variety of results emphasizes the idea that tree size, apart from directly affecting outcrossing rates through increasing flower exposition to the pollen cloud, may also be a gauge for other factors affecting mating patterns, such as reproductive effort or tree social position within the stand (Burczyk et al, 1996;González-Martínez et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…At the stand and population level, mating patterns are affected by natural factors such as population density and size, mode of pollination, flowering synchrony and phenological patterns (El-Kassaby and Jaquish, 1996;Robledo-Arnuncio et al, 2004a;Gérard et al, 2006;O'Connell et al, 2006), as well as management and silvicultural practices (Murawski et al, 1994;El-Kassaby et al, 2003). At the individual level, plant size and shape (in particular crown shape in trees), gender expression, male and female reproductive effort and within-stand social position can also affect mating patterns (Burczyk et al, 1996(Burczyk et al, , 2002Dow and Ashley, 1998;O'Connell et al, 2004;García et al, 2005;Verdú et al, 2006). Forest trees typically have a low level of domestication, and management strategies in forest tree breeding programs, in situ conservation units or ex situ conservation plantations often rely on open pollination.…”
Section: Introductionmentioning
confidence: 99%
“…Individual trees were randomly sampled in each stand. Parental trees, which had the potential of being pollinated by numerous males (Schuster and Mitton 2000;O'Connell et al 2004), were separated by a minimum of 200 m, and 500 m on average, to minimize relatedness among females. In addition, cones were collected from the upper crown only, potentially minimizing the selfing rate (O'Connell et al 2001).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Nevertheless, in wind-pollinated conifers, the mating system can be affected by population structure attributes. For example, in some conifer species, outcrossing rates are correlated with population density (Farris and Mitton, 1984;Rajora et al, 2002), family structure and tree heights (Mitton, 1992;O'Connell et al, 2004). In wind-pollinated trees, surrounding vegetation can also impede pollen dispersal, so that fragmentation can increase pollen and gene flow distances between forest trees (Young and Merriam, 1994;Dyer and Sork, 2001).…”
Section: Introductionmentioning
confidence: 99%